Pengolahan Limbah Cair Industri Tahu Menggunakan Tanaman Thypa Latifolia Dengan Proses Fitoremediasi - Disyamto, Dwi Azrul; Elystia, Shinta; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Industry tahu in Indonesia will continue to grow in line with the increase in population, due to the increasing market demand. Industry know in Indonesia will continue to grow in line with the increase in population, due to the increasing market demand. The negative impact of industrial pollution if the idea is emergence to environmental wastewater directly discharged without any treatment. To anticipate the potential impact, it is necessary efforts through a variety of alternative waste treatment waste treatment technologies are effective and efficient, one alternative is to use the process of phytoremediation. Based on the morphology of plants Thypa latifolia is suitable for processing by phytoremediation. This study aims to determine the allowance for BOD using Thypa latifolia plants in industrial wastewater know. This research used a plastic tub the size of 50cm x 36cm x 31cm, 10cm soil media thickness, media thickness 5cm sand, and gravel media 5cm thick with plant density variations Typha latifolia (0,5 g/cm2; 0,75 g/cm2, and 1 g/cm2), the variation Hidraulic Loading Rate / HLR (500 l/m2.day; 750 l/m2.day; and 1000 l/m2.day). Concentration of waste pollutant parameters analyzed include BOD, which is processed by Typha latifolia before successive concentration of 1271-1741 mg/l, while after treatment the concentration phytoremediation process successively turned into 232-996 mg/l. These results indicate that the method of the phytoremediation using Typha latifolia capable of removing concentrations of BOD, effluent industrial know. In general, variations in plant density, and HLR have a significant influence, this is evidenced by the difference in removal efficiency is much different. Plant density 1 g/cm2 with 0 g/cm2, and the HLR 500 l/m2.day to 1000 l/m2.day. Pensentase overall removal efficiency of BOD, were obtained in this study ranged respectively from 42.77 to 84.76%. The need of sample dilution to the effluent of phytoremediation waste below the standards that have been set.Keywords : Phytoremediation, Hidraulic Loading Rate (HLR), Plant Density, Waste Water Tahu Industry, Thypa Latifolia.